What Marx Means Today - Hans-Werner Sinn (Center for Economic Studies and ifo Institute (CESifo), 2017)
Marx made significant contributions to macroeconomics, laying the grounds for both Keynes'stheory of aggregate demand and Schumpeter's theory of creative destruction. His law of thetendency of the rate of profit to fall parallels Alvin Hansen's theory of secular stagnation whichhas recently received much attention among scholars studying the financial crises in Japan, theUS and the Eurozone. This article argues that part of the new stagnation does not result from anatural exhaustion of investment possibilities, but from an overly loose central bank monetarypolicy that keeps zombie banks and their zombie clients alive and blocks the emergence of newstart-up firms.
Keywords: 330